Innovating for competitive advantage in the legal profession. (2018) - Nash, Simon; Rechtschaffen, Scott; Benamram, Oz; Skinner, Kathy; Bradley, Michael; Alber, John; Hart, Duncan; Hartung, Markus; Gärtner, Arne; Tharmaraj, Deepa; Billing, Adam; Hunt, Abigail; et al.
No abstract available